The Random Utility Hypothesis and Inference in Demand Systems - Brown, Bryan W.; Walker, Mary Beth (Econometrica, 1989)
In this paper, the authors examine the consequences of adopting the random utility hypothesis as an approach for randomizing a system of demand equations. Random utility models are appealing since they allow the usual assumption of deterministic utility-maximizing behavior by each consumer to coexist with the apparent randomness across individuals that is exhibited by data. Their results show that the use of random utility models implies that the disturbances of the demand equations may not be homoskedastic, but must be functions of prices and/or income. Copyright 1989 by The Econometric Society.